THE IMPROVEMENT OF ENGLISH COMMUNICATION COMPETENCY ON SPOKEN AND WRITTEN NARRATIVE TEXT THROUGH “MOVIES CUTTING” MEDIA - Lukman Hakim (LPPM UNISDA, 2018)
The aim of this action research was improve students’ English learning result especially in communication competency. The learning process was implemented with two cycles (modes), spoken and written English. Each cycle covered four steps, namely “Building Knowledge of the field, “Modelling Text”, “Joint Construction of the Text” and “Independent/Individual Construction of the Text. The implementation of these steps was devided into 3 cycles in action research, cycle I, II and III. Each cycle covered : Planning, Implementation, Observation and Reflection. This research is for students of SMP Muhammadiyah 27 Paciran grade VIII. Motivation and scientific attitude was measured with questionaires. Activities and skill process to communicate in spoken and written were measured with rubric assesment. Cognitive domain was measured with pre-test and post-test. As the result of the research in cycle III the students average score on the Individual Text was 70 which meant ≥ the school passing grade 64. It meant that it fulfilled the achievment indicator.